Medication Use before, during, and after Pregnancy among Women with Eating Disorders: A Study from the Norwegian Mother and Child Cohort Study. - Angela Lupattelli; Olav Spigset; Leila Torgersen; Stephanie Zerwas; Marianne Hatle; Ted Reichborn-Kjennerud; Cynthia M Bulik; Hedvig Nordeng (PLoS ONE)
Introduction Little is known about medication use among women with eating disorders in relation to pregnancy. Aims To explore patterns of and associations between use of psychotropic, gastrointestinal and analgesic medications and eating disorders in the period before, during and after pregnancy. Method This study is based on the Norwegian Mother and Child Cohort Study (MoBa). A total of 62,019 women, enrolled at approximately 17 weeks' gestation, had valid data from the Norwegian Medical Birth Registry and completed three MoBa questionnaires. The questionnaires provided diagnostic information on broadly defined anorexia nervosa (AN), bulimia nervosa (BN), binge eating disorder (BED) and recurrent self-induced purging in the absence of binge eating (EDNOS-P), along with self-reported use of medication six months before, during, and 0-6 months after pregnancy. Results The prevalence of eating disorder subtypes before and/or during pregnancy was: 0.09% AN (n = 54), 0.94% BN (n = 585), 0.10% EDNOS-P (n = 61) and 5.00% BED (n = 3104). The highest over-time prevalence of psychotropic use was within the AN (3.7-22.2%) and EDNOS-P (3.3-9.8%) groups. Compared to controls, BN was directly associated with incident use of psychotropics in pregnancy (adjusted RR: 2.25, 99% CI: 1.17-4.32). Having AN (adjusted RR: 5.11, 99% CI: 1.53-17.01) or EDNOS-P (adjusted RR: 6.77, 99% CI: 1.41-32.53) was directly associated with use of anxiolytics/sedatives postpartum. The estimates of use of analgesics (BED) and laxatives (all eating disorders subtypes) were high at all time periods investigated. Conclusions Use of psychotropic, gastrointestinal, and analgesic medications is extensive among women with eating disorders in the period around pregnancy. Female patients with eating disorders should receive evidence-based counseling about the risk of medication exposure versus the risk of untreated psychiatric illness during pregnancy and postpartum.